2012
DOI: 10.1093/rheumatology/kes187
|View full text |Cite
|
Sign up to set email alerts
|

The early psoriatic arthritis screening questionnaire: a simple and fast method for the identification of arthritis in patients with psoriasis

Abstract: The EARP questionnaire is simple and fast to administer and proved robust for the identification of PsA in the dermatological setting. Dermatologists should consider the EARP for patients attending clinics, as it correlates well with early PsA diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 7 publications
3
122
1
4
Order By: Relevance
“…Скрининговые опросни-ки для использования как в дерматологической, так и в ревматологической клинической практике активно разрабатываются в последнее время за рубежом [8][9][10], од-нако в российской популяции у больных псориазом они пока не применялись.…”
Section: Osteoarticular Injury In Psoriatic Patients According To Theunclassified
“…Скрининговые опросни-ки для использования как в дерматологической, так и в ревматологической клинической практике активно разрабатываются в последнее время за рубежом [8][9][10], од-нако в российской популяции у больных псориазом они пока не применялись.…”
Section: Osteoarticular Injury In Psoriatic Patients According To Theunclassified
“…Simple and validated screening tests, such as the Psoriatic Arthritis Screening and Evaluation (PASE) tool, the Psoriasis Epidemiology Screening Tool (PEST), the Toronto Psoriatic Arthritis Screen (ToPAS) and the Early ARthritis for Psoriatic patients (EARP) questionnaire, have been assessed to determine whether people with suspected PsA should be referred to confirm the diagnosis (Table 1). 16, 17, 18, 19 Despite such tools, the paucity of data from secondary care regarding their feasibility, sensitivity and specificity, along with the lack of consensus on which tool is best, hampers their widespread clinical use. In some cases the sensitivities and specificities of the tools have been found to be lower than originally reported; when the PASE, PEST and ToPAS questionnaires were compared in the CONTEST study, it was found that they would identify cases of musculoskeletal disease other than PsA, and there was little difference between the performance of the tools 20…”
Section: Overcoming Barriers To the Early And Accurate Diagnosis Of Psamentioning
confidence: 99%
“…The ToPAS questionnaire has a broad setting including dermatologic evaluation which is unnecessary for an already dermatologically examined psoriatic patient. In this questionnaire, one third of the questions is about skin and nail symptoms of psoriasis 8 . This questionnaire has claimed its power in indicating PsA; in a prospective cross-sectional study by Reich et al…”
Section: Discussionmentioning
confidence: 99%